Somatic populations of PGT135-137 HIV-1-neutralizing antibodies identified by 454 pyrosequencing and bioinformatics - Zhu, Jiang; O’Dell, Sijy; Ofek, Gilad; Pancera, Marie; Wu, Xueling; Zhang, Baoshan; Zhang, Zhenhai; Comparative Sequencing Program, NISC; Mullikin, James C.; Simek, Melissa; Burton, Dennis R.; Koff, Wayne C.; et al. (Frontiers in Microbiology, 2012)
Select HIV-1-infected individuals develop sera capable of neutralizing diverse viral strains. The molecular basis of this neutralization is currently being deciphered by the isolation of HIV-1-neutralizing antibodies. In one infected donor, three neutralizing antibodies, PGT135-137, were identified by assessment of neutralization from individually sorted B cells and found to recognize an epitope containing an N-linked glycan at residue 332 on HIV-1 gp120. Here we use deep sequencing and bioinformatics methods to interrogate the B cell record of this donor to gain a more complete understanding of the humoral immune response. PGT135-137-gene family-specific primers were used to amplify heavy and light chain-variable domain sequences. 454 pyrosequencing produced 141,298 heavy-chain sequences of IGHV4-39 origin and 87,229 light-chain sequences of IGKV3-15 origin. A number of heavy and light chain sequences of ~90% identity to PGT137, several to PGT136, and none of high identity to PGT135 were identified. After expansion of these sequences to include close phylogenetic relatives, a total of 202 heavy-chain sequences and 72 light-chain sequences were identified. These sequences were clustered into populations of 95% identity comprising 15 for heavy chain and 10 for light chain, and a select sequence from each population was synthesized and reconstituted with a PGT137-partner chain. Reconstituted antibodies showed varied neutralization phenotypes for HIV-1 clade A and D isolates. Sequence diversity of the antibody population represented by these tested sequences was notably higher than observed with a 454 pyrosequencing-control analysis on 10 antibodies of defined sequence, suggesting that this diversity results primarily from somatic maturation. Our results thus provide an example of how pathogens like HIV-1 are opposed by a varied humoral immune response, derived from intrinsic mechanisms of antibody development, and embodied by somatic populations of diverse antibodies.